Analisis Minat Anak Petani Padi menjadi Petani di Desa Pasemah Air Keruh Sumatera Selatan - Muhammad Yamin; Lifianthi Lifianthi; Deswita Fajar Ayuningsih (Jurnal Ilmiah Membangun Desa dan Pertanian, 2023)
The sustainability of development in the agricultural sector depends on farmers as actors. There is a tendency for farmers’ children to be disinterested as farmers for a wide variety of reasons. This study aims to identify the perception of farmer children towards their interest in continuing their parents’ work as farmers and to analyze the factors that influence the chances of choosing to work as a farmer and not as a farmer. The results of this study are expected to be a reference for determining strategies that increase the interest of farmer’s children to become farmers. The data analysis method used consisted of a combination of both qualitative and quantitative analysis. This research was conducted in Muara Rungga Village, Pasemah Air Keruh District, Empat Lawang Regency, South Sumatra. This research method used the survey method. The sample frame in this study was paddy rice farmers with children aged 15-30 years. A simple random sampling method selected the total sample of 35 respondent farmers. The study results explained that the interest of farmer children to continue their parents’ work as farmers were included in the lack of interest category. The higher the age level of the farmer’s child, the greater the chances of the farmer’s child’s decision to work as a farmer, and the higher the level of education, the more significantly the events of the child choosing to work as a farmer. The findings of this study are that farm children are better educated and more skilled at using technology. The development of agriculture in the future cannot be as mediocre, and it must be completely changed according to the development of knowledge and technology so that agriculture does not seem challenging, dirty, and unattractive. Thus the farmer’s child will be interested in working as a farmer.